KEPEMILIKAN MANAJERIAL DAN PROFITABILITAS PADA NILAI PERUSAHAAN DENGAN PENGUNGKAPAN TANGGUNGJAWAB SOSIAL SEBAGAI VARIABEL PEMODERASI - Ratih, I Dewa Ayu; Eka Damayanthi, I Gusti Ayu (E-Jurnal Akuntansi; Vol 14 No 2 (2016), 2016)
The purpose of this study to determine the effect of managerial ownership and profitability in the value of the company with social responsibility disclosure as moderating variables. Non-probability sampling technique with purposive sampling method is the determination of the sample used. Manufacturing companies listed in Indonesia Stock Exchange in 2013-2014 is the population of this study in order to obtain a sample of 110 samples. Moderated Regression Analysis is used to perform data analysis. Based on the analysis found that the value of the company is affected by managerial ownership with the negative direction of the relationship, while the company's value can not be influenced by the variable profitability. Disclosure of social responsibility as well as able to moderate the effect of managerial ownership on the value of the company, while disclosure of social responsibility are not able to moderate influence on the value of the company's profitability.
Keywords: corporate values, managerial ownership, profitability, social responsibility disclosure